China’s National Interest in Providing Assistance to Indonesia in Handling the Covid-19 Pandemic: Normative and Material - Anisa Risanti Suhita; Filasafia Marsya Ma’rifat; Trisni Salsa Ramadina (Global South Review, 2021)
The scarcity of medical equipment has been inevitable since the Covid-19 pandemic emerged in 2020. Developing countries, part of the Global South, might have unfortunate conditions due to their lack of medical equipment. As part of the Global South, China has been providing assistance, having Indonesia as one of its main recipients. This study focuses on China’s assistance and vaccine cooperation with Indonesia during the COVID-19 pandemic. Since the earlier outbreak, China has provided Indonesia with multiple assistance, such as PCR test kits, medical and N95 masks, Personal Protective Equipment (PPE), and then engaging on vaccine development. The study recognizes two types of interests, the normative and material ones, shaping China’s motives. By analysing both interests, it is found that the cooperation between China and Indonesia shows that China has allowed Indonesia to be actively involved in dealing with the impact of the global pandemic. In addition to solidarity (normative interest), China’s assistance is also a form of its effort to pursue economic expansion (material interest).